Lithium‐Ion Endohedral Fullerene (Li+@C60) Dopants in Stable Perovskite Solar Cells Induce Instant Doping and Anti‐Oxidation. Issue 17 (13th March 2018) - Jeon, Il; Ueno, Hiroshi; Seo, Seungju; Aitola, Kerttu; Nishikubo, Ryosuke; Saeki, Akinori; Okada, Hiroshi; Boschloo, Gerrit; Maruyama, Shigeo; Matsuo, Yutaka
Abstract: Herein, we report use of [Li + @C60 ]TFSI − as a dopant for spiro‐MeOTAD in lead halide perovskite solar cells. This approach gave an air stability nearly 10‐fold that of conventional devices using Li + TFSI − . Such high stability is attributed to the hydrophobic nature of [Li + @C60 ]TFSI − repelling moisture and absorbing intruding oxygen, thereby protecting the perovskite device from degradation. Furthermore, [Li + @C60 ]TFSI − could oxidize spiro‐MeOTAD without the need for oxygen. The encapsulated devices exhibited outstanding air stability for more than 1000 h while illuminated under ambient conditions. Abstract : Air stability remains the most challenging limitation to commercialization of perovskite solar cells. Use of conventional Li + TFSI − dopants leads to instability because of its hygroscopic nature. Using a fullerene‐encapsulated Li + @C60 TFSI − dopant gives a 10‐fold enhancement of the air‐stability of perovskite solar cells, through the dopant's hydrophobic nature, instant oxidation of spiro‐MeOTAD, and anti‐oxidation activity.